Reasonable Scope of Kilometer Drilling in Lower Layer of Extrathick Coal Seam: A Case Study of Tingnan Coal Mine, China - Delong Zou; Xiang Zhang (Advances in Civil Engineering)
When stratified mining is adopted in high-gas and extrathick coal seam, a large amount of pressure-relief gas of the lower layer flows into the upper layer goaf along the cracks in the layer, resulting in upper layer working face to frequently exceed the gas limit. And ordinary drilling can no longer meet the requirements of the pressure-relief gas drainage of the lower layer. The 205 working face of Tingnan Coal Mine is taken as the test background in this paper, and based on the “pressure-relief and flow-increase” effect of the lower layer under the action of mining stress during the upper layer mining, the gas drainage of kilometer directional drilling in lower layer is studied. According to the distribution characteristics of support pressure before and after the working face, the pressure-relief principle, fracture development characteristics, and gas migration law of the lower layered coal body are analyzed in the process of advancing the upper layered working face in the extrathick coal seam with high gas. The maximum depth of goaf damage is calculated theoretically, and the Flac3D numerical simulation of the failure deformation of the 205 working face floor is carried out. It is found that the maximum depth of plastic failure of the lower layer is about 13 m. According to the plastic deformation of the lower layer under different vertical depths and the movement of coal and rock mass, it is determined that the reasonable range of kilometer directional drilling in the lower layer is 6–9 m below the floor vertical depth. From 15 m to 45 m in the two parallel grooves, there is no fracture failure with a sharp increase or decrease in the displacement in the local range. Meanwhile, in this part, the roof falling behind is not easy to compaction, and the displacement of the floor is large, which does not cause plastic damage. The degree of pressure relief is more sufficient, and the permeability of the lower layer is good. Therefore, drilling should be arranged as much as possible along the working face in this tendency range. The determination of reasonable arrangement range of kilometer directional drilling in extrathick coal seam provides reference index and theoretical guidance for industrial test of working face and also provides new ideas for gas control of stratified mining face in high-gas and extrathick coal seam.